Analysis Of Business Product Marketing Mix Strategies Hydroponics During The Covid-19 Pandemic In Kendari City (Nuri Horti's Hydroponic Business Case Study) - Fitra Rahmadani; Muhammad Aswar Limi; Samsul Alam Fyka (Cita konsultindo, 2023)
This study aims (1) to determine the marketing mix strategy of hydroponic business products during the Covid-19 period in Kendari City. This research was conducted in Bonggoeya, Wua-wua sub-district, Kendari City, Southeast Sulawesi. This research takes place from October 2021 to April 2022. The object of this research is the Horti Parrot hydroponic business. This research uses case study method with descriptive qualitative data analysis. This study aims to find out the marketing mix strategy used by the parrot hydroponic business during the Covid-19 pandemic by looking at product, price, place and promotion strategies. The data used in this study are primary data and secondary data. Data collection techniques are interviews and recording. From the results of research on Nuri Horti's hydroponic business products during the Covid-19 pandemic in Kendari City by meeting the demand for the types of vegetables that are in demand, giving discounts to customers, distributing their products to customers according to health protocols, and promoting products using social media WhatsApp and Facebook. Covid-19 had a positive impact on Nuri Horti's hydroponic business because during the pandemic, sales increased